PENGARUH OTAGO EXERCISE DAN GAZE STABILITY EXERCISE TERHADAP KESEIMBANGAN PADA LANJUT USIA - Isidorus Jehaman; Nur Asiyah; Sabirin Berampu; Timbul Siahaan (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2021)
The aging process is one of the life cycles experienced by every human being. However, it is a process of slowly diminishing the ability of body tissues to maintain normal structure and function. Increasing one's age has an effect on decreasing balance function. Otago Exercise and Gaze Stability Exercise to improve balance in the elderly. This research is a quantitative study with a quasi-experimental approach with a research design using pre-test and post-test. Determination of the number using purposive sampling method and obtained a sample of 14 people. Data collection was carried out by direct interviews using observation sheets. The independent variable in this study was the Otago Exercise and Gaze Stability Exercise, while the dependent variable was balance. Balance assessment using TUG> 12 seconds experienced a balance of 14 people. Statistical test using wilcoxon signed ranked test with α = 0.05. The results of the analysis show that there is a significant effect between giving Otago Exercise and Gaze Stability Exercise on the balance of the elderly, with a p value (0.001≤0.005). The conclusion of this study is that there is an effect between the provision of Otago Exercise and Gaze Stability Exercise on the balance of the elderly. The advice that can be given is that it is hoped that the patient should always do exercises to maintain body balance.